Heavy Metal Accumulation in Sediment and Removal Efficiency in the Stabilization Ponds with the Hydrocotyle ranunculoides Filter - Custodio, María (2020)
The heavy metal accumulation in the sediment and removal efficiency in stabilization ponds with Hydrocotyle ranunculoides filter were evaluated. Sediment and water were sampled in June, July and August 2018. The sediment sampling for each lagoon was conducted at three sites forming a composite sample. The water samples were collected in the tributary and effluent pipelines to determine the heavy metal concentration and removal efficiency by Hydrocotyle ranunculoides. The determination of heavy metals was performed with the method of atomic flame absorption spectrophotometry. The mean concentration of heavy metals in the sediment, in a descending order, was: Fe > Zn > Pb > Cu > Cd. The concentrations of these metals ranged from 998.0 to 1365.02, from 488.01 to 600.30, from 88.23 to 95.01, from 1.47 to 1.53 and from 0.01 to 0.13 mg/Kg, respectively. In the four stabilization ponds, the pollution factor values for Cd, Cu and Fe qualified as low pollution factor. While for Zn and Pb, they qualified as moderate pollution factors. The heavy metal removal rates from the water varied by metal.